(untitled) (Journal of Information Technologies in Education (ITE), 2015)
In the article modern presentations in relation to a structure and semantic filling of components of informative competence of future economists are analysed, placed in professional sources. The necessity of development of program tools of evident and consultative purpose, suitable for the high-quality capture by future economists by new program tools of educational and professional purpose in the conditions of the limited time, is grounded. By comparison of basic possibilities of freely expandable computer tools of creation of videos-consultations the program tool of creation of dynamic videos-consultations proper to the subject of the educational discipline «Informative systems and technologies» is select, which is foreseen by the curriculum of professional preparation of future economists. The separate standards of videos-consultations are developed and experimental verification of functioning of these program tools is carried out. In the process of pedagogical experiment were explored and compared the generalized indexes of educational progress – middle mark and coefficient of quality of educational progress of students on the most difficult themes of discipline the «Informative systems and technologies» in control and experimental groups. In the process of statistical data analysis, got as a result of pedagogical experiment, the indexes of descriptive statistics and criterion were calculated, what conclusions in relation to efficiency and fitness of the developed videos-consultations to the use in the system of forming of informative competence of future economists are formulated on the basis of.